One Brain's Response: A Reaction to Ashbrook's Juxtaposing the Brain and Belief - Wong, Tony M. (Journal of psychology and theology, 1984)
The author critiques Ashbrook's (1984) attempt at correlating findings in neuropsychology with observed patterns of belief. In the critique, it is noted that what are referred to as “known” in the neuropsychology of brain organization are primarily a collection of loose inferences lacking firm empirical support. A brief review of the current state of research on hemispheric differences is provided as a rationale for the response. It is then suggested that the weakness of the underlying hypotheses tends to undermine the originally affirmable goal of relating personal meaning with physical data.